Subducted Carbon From Mantle Plume in Mid‐Ocean Ridge Basalts - Haitao Zhang; Quanshu Yan; Xuefa Shi; Chuanshun Li; Fang Huang; Qiuyu Wen (Geophysical Research Letters)
Abstract Deciphering the Earth's deep carbon cycle, from mantle plumes to mid‐ocean ridges, remains incompletely understood. In this study, we analyze the magnesium isotope composition of basalts collected from the South Mid‐Atlantic Ridge (SMAR), which have been influenced by the off‐axis Saint Helena plume originating from the core‐mantle boundary. The magnesium isotope composition of SMAR basalts falls within a similar range (−0.22 to −0.32‰; average −0.25‰ ± 0.03‰) to that of known global oceanic basalts. However, isotope mixing calculations suggest that the lighter magnesium isotope composition in the SMAR basalts is due to the incorporation of approximately 5%–10% recycled carbonate material carried by the Saint Helena plume into the SMAR asthenosphere. This finding not only highlights the interaction between ridges and off‐axis plumes but also proposes a comprehensive model for the Earth's deep carbon cycle, spanning from the subduction zone through the core‐mantle boundary to the mid‐ocean ridge system.